A new model to predict the unsteady production of fractured horizontal wells - Zeng, Fanhui; Cheng, Xiaozhao; Guo, Jianchun; Long, Chuan; Ke, Yubiao (Penerbit Universiti Kebangsaan Malaysia, 2016)
Based on the hydraulic fracture width gradually narrows along the fracture length, with consideration of the mutual influences of fracture, non-uniform inflow of fractures segments and variable mass flow in the fracture comprehensively, a spatial separation method and time separation method were used to establish fracture horizontal well’s dynamic coupling model of reservoir seepage and fracture flow. The results showed that the calculation productivity of variable width model is higher than that of the fixed width model, while the difference becomes smaller as time increase. Due to mutual interference of the fractures, the production of outer fracture is higher than that of the inner fracture. When the dimensionless fracture conductivity is 0.1, the middle segment of the fracture dominates the productivity and local peak emerges near the horizontal well. The flow in the fracture is with the ‘double U’ type distribution. As the dimensionless fracture conductivity increase, the fractures productivity mainly through the tips and the flow in the fractures with the ‘U’ type distribution. Using the established fracture width variable productivity prediction model, one can achieve the quantitative optimization of fracture shape.